2021
DOI: 10.21608/ejp.2021.79498.1036
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Soil Type, Cyanobacterium Spirulina platensis and Biofertilizers on Controlling Damping-off, Root Rot and Wilt Diseases of Moringa (Moringa oleifera Lam.) in Egypt

Abstract: The present study was carried out under pot experiments during 2019 and 2020. Four fungi were isolated from naturally infected moringa roots. Sclerotium rolfsii was the most frequently isolated fungus, followed by Fusarium oxysporum, while Fusarium solani and Rhizoctonia solani were the least frequent ones. S. rolfsii followed by F. oxysporum were the most virulent isolated fungi that caused the highest percentages of pre-and post-emergence damping-off, root rot and/or wilt. While, F. solani showed the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It was determined that A. platensis was the most effective cyanobacteria for recovering plant height by 70.64% and 69.53%, root lengths by 92.94%, 92.94%, and the number of leaves by 76.92%, and 58.97% through the soil and foliar application, respectively. These results agree with a previous study [ 21 ], which reported that the application of A. platensis improved plant growth through polysaccharides production. The use of cyanobacteria to enhance crop growth has been proposed as a potential executive performance in crop enhancement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was determined that A. platensis was the most effective cyanobacteria for recovering plant height by 70.64% and 69.53%, root lengths by 92.94%, 92.94%, and the number of leaves by 76.92%, and 58.97% through the soil and foliar application, respectively. These results agree with a previous study [ 21 ], which reported that the application of A. platensis improved plant growth through polysaccharides production. The use of cyanobacteria to enhance crop growth has been proposed as a potential executive performance in crop enhancement.…”
Section: Discussionsupporting
confidence: 93%
“…It also can inhibit the radial Fusarium mycelial growth [ 19 ]. On the other hand, Arthrospira platensis has antifungal activity against F. oxysporum through polyphenols production in in-vitro [ 20 ] and in-vivo against Moringa Fusarium wilt [ 21 ]. Arthrospira platensis extract contains phenolics resulting in antifungal activity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2013) reported that biopesticide formulation of Anabaena spp., led to a 10% to 15% reduction in damping-off disease in tomato seedlings and significant increase in plant growth when challenged with pathogenic fungi. Similarly, the application of Spirulina platensis resulted in a reduction of root rot, root wilt and damping off symptoms in Moringa plant ( Imara et al., 2021 ).…”
Section: Microalgae As Biopesticidesmentioning
confidence: 99%
“…The inoculum of the desired tested isolates at the rate of 3.5 % (w/w) was mixed with the soil in each pot. The infested potted soil was kept moist for 5 days before planting to stimulate fungal growth and ensure its homogeneous distribution in the soil (Imara et al, 2021).…”
Section: Greenhouse Experimentsmentioning
confidence: 99%